(untitled) (PANGEEA, 2025)
A comparative outlook on the agricultural landscape in 1989 and in 2010 on the Bilag Hill and the valley of Oiejdea-Sard. The local and close horizon represents the elementary link in studies on regional geography, these contributing to the scientific fundamentation of organizing and systematizing the land. The changing of the agricultural landscape by the people doesn’t have to be looked upon as it is, but in a pluri-directional way, so that we are able to see the effects on the other natural elements and on the geographical outline in general. The understanding of these correlations as they are established and evolving in the studied area is essential in order to know the dynamics, the functioning of the whole system, to establish the quality of the environment. The human intervention non-according to the laws of nature is responsible with the chaotic rhythm of transformation of the pattern of slopes on the Bilag Hills. Thus, degraded landscapes occur, characterized by the essential changing of some elements or their total cancellation from the territorial pattern, so disrupting the natural equilibrium. Abandoned agro-terraced vineyards were exposed to quick. The gathering of sewers caused the rise in the water level and the marshing of some agricultural areas; the exacavation in the Ampoi caused the fall of the water level in the wells in the village of Sard; deforestation caused further erosion; the building of economic sites in the river enhances the peril of floods. The equilibrium that existed in 1989 was disrupted between 1989 and 2010 by irresponsible activities, lack of modern agricultural machines, money, use of chemicals, all these causing the of the land. Key words: organizing and systematizing the land, agricultural landscape, human intervention, degraded landscapes, erosion, negative change.